C-Type Natriuretic Peptide Induces Anti-contractile Effect Dependent on Nitric Oxide, Oxidative Stress, and NPR-B Activation in Sepsis - Pernomian, Laena; Prado, Alejandro F.; Silva, Bruno R.; Azevedo, Aline; Pinheiro, Lucas C.; Tanus-Santos, José E.; Bendhack, Lusiane M. (Frontiers in Physiology, 2016)
Aims: To evaluate the role of nitric oxide, reactive oxygen species, and natriuretic peptide receptor-B activation in C-type natriuretic peptide-anti-contractile effect on Phenylephrine-induced contraction in aorta isolated from septic rats. Methods and Results: Cecal ligation and puncture surgery was used to induce sepsis in male rats. Vascular reactivity was conducted in rat aorta and resistance mesenteric artery. Measurement of survival rate, mean arterial pressure, plasma nitric oxide, specific protein expression and localization were evaluated. Septic rats had a survival rate about 37% at 4h after the surgery, and these rats presented hypotension compared to control-operated (Sham) rats. Phenylephrine-induced contraction was decreased in sepsis. C-type natriuretic peptide induced anti-contractile effect in aortas. Plasma nitric oxide was increased in sepsis. Nitric oxide-synthase but not natriuretic peptide receptor-B expression was increased in septic rat aortas. C-type natriuretic peptide-anti-contractile effect was dependent on nitric oxide-synthase, reactive oxygen species and natriuretic peptide receptor-B activation. Natriuretic peptide receptor-C, protein kinase-Cα mRNA and basal nicotinamide adenine dinucleotide phosphate-dependent reactive oxygen species production were lower in septic rats. Phenylephrine and C-type natriuretic peptide enhanced reactive oxygen species production. However, stimulated reactive oxygen species production was low in sepsis. Conclusion: C-type natriuretic peptide induced anti-contractile effect on Phenylephrine contraction in aortas from Sham and septic rats that was dependent on nitric oxide-synthase, reactive oxygen species and natriuretic peptide receptor-B activation. Keywords: C-type natriuretic peptide – Sepsis – Natriuretic peptide receptor B – Reactive oxygen species – Nitric oxide- Phenylephrine-induced contraction